Herbal medicine: Safety and quality concerns - Khamsah Suryati, Mohd (2017)
Herbal products are complex mixtures of organic chemicals that may come from any raw or processed part of a plant or the parts themselves, such as leaves, stem, flowers, roots and seeds. It is estimated that 37% of sales of the world’s pharmaceutical products originate from natural raw material. It appears that dependence upon herbal now are widely acknowledged by the general public and endorsed by the medical profession at large. Current law defined herbs as dietary supplement. In this case, the evidence of efficacy and demonstration of safety not a vital requirement as pharmaceutical drugs. Aligned with increase in worldwide consumption, the safety of herbal medicine is subject of concern. Although herbs are often perceived as “natural”, “green” and “back to nature” rhetoric, many side effects have been reported owing to contaminants, adulteration, or interaction with other drugs. The socio-economic changes plus the technological advances, commercial factors, consumers’ preferences and changing lifestyles have influenced the way herbal drug are being manufactured and distributed. A various range of botanical medicine is now available as over-the-counter (OTC) products. Thus, just like pharmaceutical industry, it has become utmost importance to assure quality, safety and efficacy of herbal product through the whole manufacturing process.